A basic vehicle dynamics model for driving simulators. (1st January 2013) - Bruzelius, F.; Gomez Fernandez, Jorge; Augusto, Bruno
Driving simulators are a useful research tool in studies of vehicle and transport-related human machine interface. A vital part of the driving simulator is the vehicle dynamics model. In the present paper, such a model is developed. The model implements basic first order phenomena, but is yet complete in the terms of modelled parts of the vehicle. A major challenge is the trade-off between simplicity and accuracy imposed by the capabilities of the driving simulators motion platform. The modelling language Modelica was used for readability reasons. The model has been validated toward both measurements of a real car and subjectively in a driving simulator. It is shown that the model is well capable of fulfilling the imposed requirements, despite its simplicity. The model is open and available upon request.